Repeated nitrogen fertilization enhances Scots pine growth and carbon uptake without persistent long-term effects in boreal forests - Palvi, Anni; Martínez-García, Eduardo; Szejner, Paul; Rinne-Garmston, Katja T; Young, Giles H F; Sahlstedt, Elina; Mäkipää, Raisa; Lehtonen, Aleksi (Oxford University Press, 2025)
Nitrogen (N) fertilization is known to enhance tree biomass production and carbon (C) assimilation in N-limited boreal forests. Yet, the long-term effects of repeated N applications remain limited. Here, we evaluate the impact of repeated N fertilization at 10-year intervals over six decades on a nutrient-poor Scots pine (Pinus sylvestris L.) forest in Central Finland. The analysis encompassed both short-term (single N-addition) and long-term (multi-decadal repeated N-additions) responses of basal area increment (BAI) and carbon isotope composition in tree rings (δ13C) from fertilized and control plots from 1960 to 2022. Furthermore, needle mass and chemistry were investigated, and stand-level nitrogen-use efficiency (NUE, amount of stem volume or tree C increased per unit mass of N added) estimated. We found that a single N-addition had a positive short-term effect on the tree ring δ13C during the first 2 years after fertilization. This suggests a combined effect on increase in photosynthetic activity and stomatal conductance, likely driven by greater needle mass and higher N content. Basal area increment showed a delayed but rapid increase, attributable to enhanced needle mass from improved photosynthesis, reaching its peak 2 years after fertilization, and then persisting for a period of 4–7 years. However, by the end of each decadal fertilization cycle, BAI and δ13C values in N treatment reached those of control, demonstrating no lasting site carry-over effects. The mean decadal NUE for the tree stem volume was 0.16 m3 per kg N added, indicating a significant degree of N retention in the forest ecosystem. After six decades, the cumulative impact of repeated fertilization led to a 47% increase in BAI in fertilized plots compared with controls, demonstrating the efficacy of accumulated short-term growth enhancements. Our findings highlight the potential of repeated N fertilization as an effective forest management practice to support the bioeconomy and mitigate climate change in nutrient-poor boreal forests.
Keywords: climate change; forest management; forest productivity; intrinsic water-use efficiency; nutrient limitation; wood production